2021
DOI: 10.1088/1751-8121/abf3e9
|View full text |Cite
|
Sign up to set email alerts
|

A Green’s function approach to the linear response of a driven dissipative optomechanical system

Abstract: In this paper, we first try to shed light on the ambiguities that exist in the literature in the generalization of the standard linear response theory (LRT) which has been basically formulated for closed systems to the theory of open quantum systems in the Heisenberg picture. Then, we investigate the linear response of a driven-dissipative optomechanical system (OMS) to a weak time-dependent perturbation using the so-called generalized LRT. It is shown how the Green’s function equations of motion of a standard… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 69 publications
0
18
0
Order By: Relevance
“…where ω pc = ω p − ω c is the detuning between the probe and coupling lasers frequencies In Ref. [33], the linear response of a standard OMS has been investigated in the framework of the GLRT. On the other hand, in Secs.II and III, it was shown that a hybrid OMS consisting of an atomic BEC behaves effectively as a standard OMS.…”
Section: Linear Response Of Hybrid Oms In the Framework Of Glrtmentioning
confidence: 99%
See 3 more Smart Citations
“…where ω pc = ω p − ω c is the detuning between the probe and coupling lasers frequencies In Ref. [33], the linear response of a standard OMS has been investigated in the framework of the GLRT. On the other hand, in Secs.II and III, it was shown that a hybrid OMS consisting of an atomic BEC behaves effectively as a standard OMS.…”
Section: Linear Response Of Hybrid Oms In the Framework Of Glrtmentioning
confidence: 99%
“…Recently, several researches have been conducted to generalize the SLRT to the theory of open quantum systems both in the Schrödinger picture through the master equation approach [29][30][31] and in the Heisenberg picture through the quantum Langevin equations (QLEs) [32,33]. In the so-called generalized linear response theory (GLRT) the linear response of * a dalafi@sbu.ac.ir an open quantum system to an external time-dependent perturbation is investigated while the effect of the environment is taken into account in the mathematical modeling as a multimode quantum field with an infinite number of degrees of freedom which interacts with the open quantum system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Optomechanical systems (OMSs) have been exploited in different areas of quantum technologies, such as quantum information processing and communication [1][2][3][4], quantum memories [5,6], reversible microwave-to-optics converters [7][8][9][10][11], microwave circulators [12,13], quantum correlations [14][15][16][17][18], quantum squeezing [19,20], as well as in fundamental physics [21][22][23][24][25][26][27][28][29][30]. Also, optomechanical-based sensors have been recognized as optimal candidate for the detection of minuscule forces at the quantum limit [31] such as observation of gravitational waves [32].…”
Section: Introductionmentioning
confidence: 99%